(untitled) - Whittington, Ray (Boston, 2014)
Principles of Auditing presents concepts clearly and proactively monitors changes in auditing making the relationship between accounting and auditing understandable. The 16th edition maintains the organization and balance sheet orientation, while adding and enhancing topics of Risk, Assurance Services, Fraud, E-Commerce, and the latest auditing standards to meet the needs of the current marketplace
Keywords: Auditing,Kiểm toán